Enhancing Learning Outcomes: A Study on the Development of Higher Order Thinking Skills based Evaluation Instruments for Work and Energy in High School Physics - Dian Artha Kusumaningtyas; Muhamatsakree Manyunu; Efi Kurniasari; Annisa Nabilla Awalin; Rita Rahmaniati; Amalia Febriyanti (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2024)
This study aimed to enhance student learning outcomes in the field of work and energy within senior high schools through the development of evaluation instruments based on higher-order thinking skills (HOTS). Higher-order thinking encompasses advanced cognitive abilities such as analysis, evaluation, and creative problem-solving. The evaluation instrument created was meticulously designed to encourage students to think critically, solve intricate problems, and apply physics principles to real-world scenarios. The research methodology employed the development research approach. The instrument development process comprised several stages, including needs analysis, instrument design, validation, and revision. To ensure the instrument's precision and validity, experts in physics education and educational evaluation actively participated in the validation process. The resulting evaluation instrument included a combination of multiple-choice questions and open-ended responses. Students underwent assessment using this instrument following their study of work and energy. Evaluation data were subsequently analyzed through both quantitative and qualitative methods. The outcomes demonstrated a significant improvement in student learning achievements concerning work and energy when using evaluation instruments founded on higher-order thinking. Students who utilized this instrument exhibited superior critical thinking skills, enhanced problem-solving abilities, and an improved capacity to apply physics concepts in real-life situations. This study provides invaluable recommendations for educators and curriculum developers, advocating for the adoption of higher-order thinking-based evaluation instruments in high school physics education. Such an approach has the potential to bolster students' higher-order thinking capabilities and augment their learning outcomes in the context of work and energy. In summary, the successful development and validation of the HOTS based evaluation instrument for 10th-grade high school physics students studying work and energy attest to its viability. Rigorous evaluations from both subject matter experts and media specialists consistently affirmed its suitability across diverse aspects, encompassing appearance, content, and language. Educators, who play a pivotal role in instrument implementation, lauded its effectiveness in teaching work and energy concepts. Positive feedback from students, the primary beneficiaries of this evaluation instrument, underscores its widespread acceptance and appropriateness. In sum, this research underscores the instrument's strong validity and practicality for evaluating students' grasp and application of work and energy principles in high school physics, endorsing its capacity to augment learning outcomes.